2017
DOI: 10.1038/s41598-017-11080-9
|View full text |Cite
|
Sign up to set email alerts
|

Noble UV protective agent for Bacillus thuringiensis based on a combination of graphene oxide and olive oil

Abstract: The focus of this study is investigating the performance of graphene oxide (GO) in the protective effect of olive oil on Bacillus thuringiensis (Bt) after being exposed to UV radiations. Biological pesticides Bt subsp. Kurstaki is one of the most important biological control agents. We compared the protective effect of two UV protectant; GO and olive oil and also the combination of both, on the stability of the formulation of Bt after exposure to UV radiations. Spore viability was measured for protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 39 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…GO nanosheets were added to the oil phase as a protective agent against UV. The UV absorption of GO has been shown by our previous researches 20 . Although the antibacterial activity of GO has been confirmed in some studies, the size of the nanosheets has been identified as an influencing factor on their antibacterial property.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…GO nanosheets were added to the oil phase as a protective agent against UV. The UV absorption of GO has been shown by our previous researches 20 . Although the antibacterial activity of GO has been confirmed in some studies, the size of the nanosheets has been identified as an influencing factor on their antibacterial property.…”
Section: Discussionmentioning
confidence: 74%
“…UV resistance results shown better efficiency of the sludge-based Bt formulations in comparison to the half-life of conventional Bt formulations ranging from 16 h to 2 days in field conditions 8 . In our previous study, we showed the highest mortality of irradiated combination formulation of GO/olive oil on second-instar larvae E. Kuehniella was 68.89% 20 . In this study, the same parameter for 96 h Irradiation of 0.045% GO encapsulated is 70.68%.…”
Section: Discussionmentioning
confidence: 84%
“…At the moment, the spore-forming bacterium B. thuringiensis , producing insecticidal crystal proteins, is the prevalent commercial agent for insect pest control [ 18 , 19 ]. Sensitivity of the majority of biopesticides based on commercial strains to temperature regime, atmospheric precipitations, and other conditions put bounds on their extensive use.…”
Section: Discussionmentioning
confidence: 99%
“…The practical application of B. thuringiensis has been promoted as a result of pests’ resistance to chemical insecticides [ 16 , 17 ]. B. thuringiensis strains are vulnerable to UV light and flushing by rain precipitation [ 18 , 19 ]. Currently, the search for endophytic microorganisms producing insectotoxins, which inhabit the internal tissues of plants and are less influenced by environmental factors and more integrated in plant metabolism than rhyzo- and fillospheric PGPB, is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…The wrinkles and creases on the surface of GO may be due to the presence of randomly distributed oxygen functionalities. [ 31, 32 ] Figure 4(C) representing TG obtained after thermal treatment of GO shows that most of the layers are crumpled, wrinkled and found to be exfoliated. This can be attributed to the defects arising from the structural reorientation of carbon sheets as a result of decomposition of oxygen containing functionalities to CO or CO 2 .…”
Section: Resultsmentioning
confidence: 99%